Analisis Deiksis Cerpen dalam Buku Bahasa Indonesia Kelas VIII Kurikulum Merdeka - Nur Saidah; Ras Tuti Analiah; Ananda Putri Risang Ayu; Wiwik Fitriyani; Arif Setiawan; Asep Purwo Yudi Utomo; Dyah Prabaningrum (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research examines deixis in short stories in Buku Bahasa Indonesia Kelas XIII Kurikulum Merdeka, which aims to identify and describe deixis, which is divided into personal, place, time, discourse, and social deixis. The method used is a qualitative and pragmatic descriptive approach, with the data source being short stories in the Buku Bahasa Indonesia Kelas VIII Kurikulum Merdeka. The analytical method in this research is the agih method, which uses data in the form of fragments of words and phrases contained in the short story